1976
DOI: 10.1007/bf01278605
|View full text |Cite
|
Sign up to set email alerts
|

Influence of redox potential on the glucose catabolism of chemostat grownBacillus licheniformis

Abstract: The effect of the redox potential on the by-production of acetic acid by Bacillus licheniformis grown in a chemostat has been studied.It was demonstrated that B.licheniformis produced acetic acid when it was grown at a low growth rate, low oxygen supplies, and low redox potentials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

1978
1978
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…From (5) it can be seen that for an equilibrium the Ela will decrease by 14.8 mV for a decrease in ao~ by a factor of 10. This is in opposition to what has been reported by several authors (Schuldiner et al, 1966;Jacob, 1971 ;Kjaergaard, 1976). However, the latter two refer to Schuldiner et al and obviously they have not calculated the value themselves.…”
Section: Theory Of Redox Potentialcontrasting
confidence: 66%
See 1 more Smart Citation
“…From (5) it can be seen that for an equilibrium the Ela will decrease by 14.8 mV for a decrease in ao~ by a factor of 10. This is in opposition to what has been reported by several authors (Schuldiner et al, 1966;Jacob, 1971 ;Kjaergaard, 1976). However, the latter two refer to Schuldiner et al and obviously they have not calculated the value themselves.…”
Section: Theory Of Redox Potentialcontrasting
confidence: 66%
“…However, it must be emphasized that the extraceUular redox potential is different from the redox potentials that are measured in cell-free extracts and that are closely related to the redox potentials for the different steps in the respiratory chain (Zs.-Nagy and Ermini, 1972). Kjaergaard (1976) showed recently that the ineffective by-production of acetic acid by Bacillus licheniformis depended heavily on the redox potential. Unlike in most of the preceding studies the redox potential was changed by changing something other than the aeration and addition of redox chemicals.…”
Section: Redox Potential In Microbial Growth Systemsmentioning
confidence: 99%
“…In the past two decades, culture redox potential (CRP) measurements in aerobic and microaerobic fermentation have been primarily based on the assumption that extracellular redox potential readings are a function of the intracellular redox environment. Another motivation for these measurements has been that CRP can be used to estimate extremely low levels of dissolved oxygen (DO) (Wimpenny, 1969; Daniels et al, 1970; Kjaergaard, 1976). Many studies have been conducted to investigate the effects of CRP on cell metabolism in microaerobic environments, and it has been observed that different values of CRP during fermentation can lead to changes in endproduct formation (Wimpenny, 1969; Wimpenny and Necklen, 1971; Shibai et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…He reported that the redox potential increased under a more aerobic condition and that it influenced TCA cycle enzymes, cytochrome, ATP pool, growth yield, and hydrogenase activity. It was also found that the redox potential influenced the simultaneous biosynthesis of the antibiotics levorin A and B (Kjaeergaard, 1976). Levorin A was preferably produced at a high redox potential, and levorin B compound was produced at a lower redox potential.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of previous studies, redox potential was used for estimating extremely low dissolved oxygen concentration (DOC) under almost anaerobic conditions (below the lower limit of DO probes) due to its strong dependency on DOC (Kjaeergaard, 1976;Wimpenny, 1969;Srinivas et al, 1988).…”
Section: Introductionmentioning
confidence: 99%